Rhabdomyolysis in a HIV-infected Patient Following the Addition of Raltegravir, A Case Report with Review of the Literature - L. Johnson, Anna; Garavaglia Wilson, Alexandria (Journal of Clinical Research In HIV AIDS And Prevention, 2013)
Antiretrovirals have traditionally been associated with much toxicity. Newer antiretrovirals are considered much less toxic relative to older antiretrovirals. Upon its FDA-approval in 2009, raltegravir’s adverse drug reaction profile was found to be similar to placebo. However, recently there have been reports of increased creatine kinase and rhabdomyolysis following the initiation of raltegravir. We describe a 52-year-old, African-American man who developed rhabdomyolysis after starting raltegravir for HIV. Rhabdomyolysis resolved upon discontinuation of raltegravir. Use of the Naranjo adverse drug reaction probability scale indicated a probable relationship (score of 6). Although raltegravir is a well-tolerated antiretroviral, clinicians should be aware of the possibility of rhabdomyolysis when prescribing this medication.
Keywords: raltegravir; rhabdomyolysis; HIV